The Crystal Structure of Orthocetamol Solved by 3D Electron Diffraction. Issue 32 (11th July 2019) - Andrusenko, Iryna; Hamilton, Victoria; Mugnaioli, Enrico; Lanza, Arianna; Hall, Charlie; Potticary, Jason; Hall, Simon R.; Gemmi, Mauro
Abstract: Orthocetamol is a regioisomer of the well‐known pain medication paracetamol and a promising analgesic and an anti‐arthritic medicament itself. However, orthocetamol cannot be grown as single crystals suitable for X‐ray diffraction, so its crystal structure has remained a mystery for more than a century. Here, we report the ab‐initio structure determination of orthocetamol obtained by 3D electron diffraction, combining a low‐dose acquisition method and a dedicated single‐electron detector for recording the diffracted intensities. The structure is monoclinic, with a pseudo‐tetragonal cell that favors multiple twinning on a scale of a few tens of nanometers. The successful application of 3D electron diffraction to orthocetamol introduces a new gold standard of total structure solution in all cases where X‐ray diffraction and electron‐microscope imaging methods fail. Abstract : Tiny twins, big challenges : For the first time, 3D electron diffraction was used to solve the unknown crystal structure of orthocetamol, a pharmaceutical compound. Previously, the structure could not be solved with other diffraction techniques because the system does not form single crystals but favors multiple twinning on a scale of a few tens of nanometers.